Elements of National Thinking in The Philosophical Heritage of Tilab Mahmudov (International Journal of Scientific Trends, 2026)
This article examines the elements of national thinking in the philosophical heritage of Tilab Mahmudov. The thinker’s views on national values, moral and spiritual education, aesthetic consciousness, and youth development are analyzed from a scientific and theoretical perspective. Particular attention is paid to the issues of national identity, historical memory, and cultural heritage reflected in his works. The study substantiates that Tilab Mahmudov’s philosophical ideas serve as an important source for the development of national thinking in contemporary society.